Clinical Transition: RN to BSN Students' Perceptions of Their Abilities to Meet Program Outcomes. Issue 6 (20th November 2022) - Connerton, Charlotte S.; Hand, Mikel W.; Wooton, Angela K.
Abstract : Supplemental digital content is available in the text. Abstract: The purpose of this study was to analyze RN to BSN students' perceptions of their abilities to meet program outcomes through their clinical experiences with a clinical teaching associate and after assuming responsibility for planning and directing clinical learning activities. A mixed-methods approach was used. Most students (87 percent) reported achievement of program outcome measures. Students demonstrated real-world learning and application through clinical experiences and successfully met program outcomes.